Perspective: IL-15 cytokine-armored NK cells as ready-to-use immunotherapy for diverse malignancies: therapeutic potential and toxicity risks - Baughan, Scott L.; Folsom, Timothy; Johnson, Matt; Kreuger, Joshua; Webber, Beau R.; Moriarity, Branden S. (Frontiers in Immunology, 2025)
Natural killer (NK) cells have been engineered to express chimeric antigen receptors (CARs) to enhance their cytotoxic capabilities through CAR-mediated activation, a strategy that has yielded promising advancements in cancer treatment in recent pre-clinical and clinical trials. However, the use of CAR-NK cells for the treatment of solid tumors has presented challenges due to limited in vivo CAR-NK efficacy, expansion, persistence, and the suppressive tumor microenvironment. Many groups have developed IL-15 cytokine-armored CAR-NK therapeutics targeting various cancers to overcome these challenges. However, preclinical in vivo studies using immunodeficient mice have encountered instances of significant toxicity without evidence of cytokine release syndrome. The lack of an intact immune system likely allows for unchecked in vivo expansion of cytokine armored CAR-NK cells, leading to early mortality in immunodeficient mice following treatment with these cells. We speculate that the use of humanized mice will allow for engraftment of tumor and alleviate cytokine armored CAR-NK toxicity, thereby allowing for effective assessment of CAR-NK efficacy in the absence of toxicity.